Penerapan Standar Profesional Akuntan Publik Dalam Perencanaan Audit KAP XYZ - Shavira Aisyah Maharani; Endah Susilowati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine audit planning applied by XYZ Accounting Firm and comparing it with audit planning estabilished by Public Accountant Professional Standards in Indonesia. Descriptive qualitative method is used involving interview and oservation techniques for data collections. The results state that the audit planning carried out by XYZ Accounting Firm consists of 8 stages, namely: 1) Client acceptance and initial audit planning; 2) Understanding the business entity; 3) Assessing business risks; 4) Establishing preliminary analytical procedures; 5) Determining materiality; 6) Understanding the internal control system; 7) Assess the risk of fraud and; 8) Develop an audit program. After comparing the data, it can be concluded that the implementation of audit planning implemented by XYZ Accounting Firm is in accordance with the audit planning established by the Public Accountant Professional Standards.